2012
DOI: 10.1002/jbmr.1803
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin antibody treatment improves bone mass, bone strength, and bone defect regeneration in rats with type 2 diabetes mellitus

Abstract: Type 2 diabetes mellitus results in increased risk of fracture and delayed fracture healing. ZDF fa/fa rats are an established model of type 2 diabetes mellitus with low bone mass and delayed bone healing. We tested whether a sclerostin-neutralizing antibody (Scl-AbVI) would reverse the skeletal deficits of diabetic ZDF rats. Femoral defects of 3 mm were created in 11-week-old diabetic ZDF fa/fa and nondiabetic ZDF þ/þ rats and stabilized by an internal plate. Saline or 25 mg/kg Scl-AbVI was administered subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 35 publications
4
105
0
2
Order By: Relevance
“…To date, however, there are no human data on the effect of intermittent PTH in T1DM patients. Sclerostin antibody has been tested in animal models with T2DM, where it increased bone mass and strength, but not in the setting of T1DM (125). Unfortunately no clinical studies are yet available to confirm this in humans.…”
Section: Fracture Preventionmentioning
confidence: 99%
“…To date, however, there are no human data on the effect of intermittent PTH in T1DM patients. Sclerostin antibody has been tested in animal models with T2DM, where it increased bone mass and strength, but not in the setting of T1DM (125). Unfortunately no clinical studies are yet available to confirm this in humans.…”
Section: Fracture Preventionmentioning
confidence: 99%
“…At later time points, this leads to higher mineral content in the abundantly formed new bone, thereby potentially increasing mechanical stability. Furthermore, early reports that successfully used Sost antibody treatment to promote fracture healing relied heavily on models that primarily healed by intramembranous bone formation [94,140,152,153]. This suggested that SostAb may be beneficial in problematic fracture healing that results from poor osteogenesis; however, Li et al (2011) [154] reported fracture repair in an endochondral model in Sost -/-mice, and Feng et al (2015) [155] reported similar results with Sost antibody treatment, suggesting that fracture repair may benefit from early intervention by reducing sclerostin levels, rather than only during osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, murine Sost antibodies increase bone mineral density (BMD) in ovariectomized rats, and decrease fracture risk [93], revealing that SOST antibody may also be beneficial for those with osteoporosis. Sost antibody treatment on T2DM rats with a low bone mass phenotype has also revealed increased bone formation, however this effect has not been examined in T1DM mice [94]. Sost antibody have also shown an anabolic effect in fracture healing with enhanced bone formation and is mechanically stable [95].…”
Section: Sost As a Wnt Antagonist And Sost Antibodymentioning
confidence: 99%
See 1 more Smart Citation
“…In post hoc analysis of the FIT alendronate and HORIZON zoledronic acid trial, fracture reduction was similar in participants with and without diabetes [69]. Teriparatide and sclerostin antibodies increase BMD in Zucker diabetic rats, but the rats' bone phenotype is different from human T2DM, and there is not yet available information on these drugs in humans with T2DM [70,71].…”
Section: Fracture Risk Assessment and Osteoporosis Treatment In T2dmmentioning
confidence: 99%